2020
DOI: 10.1186/s42400-019-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

An emerging threat Fileless malware: a survey and research challenges

Abstract: With the evolution of cybersecurity countermeasures, the threat landscape has also evolved, especially in malware from traditional file-based malware to sophisticated and multifarious fileless malware. Fileless malware does not use traditional executables to carry-out its activities. So, it does not use the file system, thereby evading signature-based detection system. The fileless malware attack is catastrophic for any enterprise because of its persistence, and power to evade any anti-virus solutions. The mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(29 citation statements)
references
References 32 publications
(37 reference statements)
0
24
0
Order By: Relevance
“…Another possible mechanism to evade detection is the use of a fileless architecture, which is becoming a relevant trend. For instance, the recent survey [22] provided an overview of the fileless malware and related detection techniques. Owing to its nature, this class of threat remains unnoticed by the traditional file-focused detection systems; thus, the authors concluded that the detection of fileless malware may require the use of forensic tools.…”
Section: A Surveys On Malware Analysis and Evasionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another possible mechanism to evade detection is the use of a fileless architecture, which is becoming a relevant trend. For instance, the recent survey [22] provided an overview of the fileless malware and related detection techniques. Owing to its nature, this class of threat remains unnoticed by the traditional file-focused detection systems; thus, the authors concluded that the detection of fileless malware may require the use of forensic tools.…”
Section: A Surveys On Malware Analysis and Evasionmentioning
confidence: 99%
“…• limited interest in information hiding: as shown, only one recent work dealt with information hiding (specifically, in the context of mobile devices). As modern mal- [23] x x x x x [16] x x x x x [24] x x [22] x x fileless [31] x adversarial ML [17] x tools [25] x AI [14] x x x evasion, tools [34] x x x evasion [18] x x evasion [21] x x APT [28] x x cybersecurity [19] x evasion [26] x x x x [27] x x cybersecurity [36] x x x visualisation [30] x x [11] x x behavior analysis, visualisation [12] x analysis [37] x x [33] x x x evasion [29] x x x [15] x x x x x [20] x x stealth malware [32] x x x C&C communication [35] x x x OS openness [38] x x [39] x visualisation ware is increasingly exploiting some form of steganography, information hiding and obfuscation to launch attacks or exfiltrate data [42], [43], this consolidated trend should be taken into account. • lack of sufficient coverage of new threats: despite the vivacity of the topic, many works continue to focus on the "legacy" hazards, e.g., phishing.…”
Section: Contributions and Survey Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…Hence the detection complexity becomes too high for Fileless malware. The possibility of investigating Fileless malware is only limited to analysis of the behavior of the system using the snapshots of In-memory processes, which is considered here as Memory based analysis [16]. Information retrieval theory is applied with a dynamic analysis to extract API calls and system calls to classify malicious programs.…”
Section: Related Workmentioning
confidence: 99%